Reflections on the concept of micropractice (Revista Apotheke, 2023)
This article consists of presenting a theoretical survey and methodological notes on the concept of micropractice, considering the teaching and learning space in the visual arts and the painting studio as a laboratory. Concepts about the term micropractice in disparate and correlated areas of knowledge are considered, however, the theoretical consolidation studied highlights the significance of the methodological procedure in relation to art and art education, and considers micropractice (pictorial), from the introduction to its conceptual establishment (theoretical and practical) in the context of the Apotheke Painting Studio, which is configured as a Permanent Extension Program linked to the University of the State of Santa Catarina and in a growing perspective with interdepartmental, interinstitutional and international actions, which make up theoretical and methodological improvement networks. In all approaches, the originality of the concept stands out in art as experience.
Keywords: Visual arts; Painting teaching; Experience; Micropractice